1983
DOI: 10.1007/bf00399500
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic systems in lactic acid bacteria

Abstract: The proteolytic systems of lactic acid bacteria are important as a means of making protein and peptide N available for growth and as part of the curing or maturation processes which give foods their characteristic rheological and organoleptic properties. The proteolytic systems of lactic acid bacteria are described in relation to their growth and their functions in protein-rich foods. Their role in the manufacture of milk products is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
1
11

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(136 citation statements)
references
References 60 publications
4
114
1
11
Order By: Relevance
“…Study on the regulatory mechanism of proteinases in lactococci revealed that the presence of amine acids or peptides at high extracellular concentration may prevent proteinase synthesis (Law and Koistand, 1983). However, synthesis of the cell-wall proteinases appears to be regulated by amino acids or peptides at the level of rnRNA translation.…”
Section: Proteinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Study on the regulatory mechanism of proteinases in lactococci revealed that the presence of amine acids or peptides at high extracellular concentration may prevent proteinase synthesis (Law and Koistand, 1983). However, synthesis of the cell-wall proteinases appears to be regulated by amino acids or peptides at the level of rnRNA translation.…”
Section: Proteinasesmentioning
confidence: 99%
“…An indirect method, which involves cell fractionation using lysozyme or Iysin (Exterkate, 1976b;Law and Koistand, 1983;Ohmiya and Sato, 1975;Thomas el al, 1974) has always been used. Cell wall components were released in the absence of intracellular marker enzymes and proteinase activity was detected in spheroplast supernatant fractions.…”
Section: • • •mentioning
confidence: 99%
“…Due to the rather low content of free essential amino acids in milk they are dependent on their proteolytic abilities to degrade milk casein. Lactobacilli possess a complex proteolytic system composed of proteinases and a variety of peptidases (Abo-Elnaga & Plapp, 1987;Law & Kolstadt, 1983;Thomas & Pritchard, 1987), which act in a cascade to hydrolyse casein to small transportable peptides and amino acids. The quality of dairy products The GenBanWEMBUDDBJ accession number for the nucleotide sequence reported in this paper is 231377.…”
Section: Introductionmentioning
confidence: 99%
“…They contribute to the flavour and texture of fermented milk products (Fox, 1989;Law & Kolstad, 1983;Thomas & Mills, 1981). Much is known about the proteolytic systems of the lactococci.…”
Section: Introductionmentioning
confidence: 99%